Pengukuran Kepuasan Pelanggan Menggunakan Servqual di Spinelli Coffee Gandaria - Fitricia Pasaribu, Nami (Bina Nusantara University, 2013)
Customers satisfaction to service and or tangible products provide by coffee shop could be a distinctive phenomenon to a company. To give in-depth insight for this issue, the study and SERVQUAL approach was valued to help Spinelli Coffee to give their best service. Using interview and questtionaire, it is hoped to bridgecustomers needs to providers. In a hope of customers expectation and perceive synchronization onto the service. Result of innovative output such as on-line feedback from customers to the company to acknowledge market demand was an intetion from this study.